Pengembangan Kemasan UMKM Berbasis Sistem SPKP (Sistem Penilaian Kurasi Produk) untuk Meningkatkan Brand Value Melalui Rumah Kurasi - Anggraini, Widya Eka Putri; Safitri, Shalsa Aida; Oktaviana, Dika; Yukonin, Eja Sabina; Yaqin, Moh. Haqqul; Nikmah, Lailatun; Putri, Rahma Aulia; Hidayah, Islamiati Hidayah (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
This community service activity aims to improve the quality of MSME product packaging through the implementation of the Product Curation Assessment System (PCAS) at Rumah Curasi in order to increase competitiveness and brand value. The main problem faced by MSMEs is the low quality of packaging, which affects their ability to compete in modern and international markets. The method used is Participatory Action Research (PAR), with stages of socialization, mentoring, training, and evaluation. In its implementation, this activity involves MSME actors in the curation process, providing packaging design training, and intensive consultation to meet the criteria of legality, quality, and aesthetics. The results of the activity showed a significant increase in MSME actors' understanding of the importance of packaging as a branding strategy. As many as 85% of participants succeeded in developing more attractive packaging that meets market standards. This has a positive impact on increasing consumer purchasing interest, market potential, and MSME competitiveness at the local and international levels.